Antiviral Profiling of C-18- or C-19-Functionalized Semisynthetic Abietane Diterpenoids (2022)
ABSTRACT: Viral infections affect several million patients annually. Although hundreds of viruses are known to be pathogenic, only a few can be treated in the clinic with available antiviral drugs. Naturally based pharmacotherapy may be a proper alternative for treating viral diseases. Several natural and semisynthetic abietane-type diterpenoids have shown important antiviral activities. In this study, a biological evaluation of a number of either C-18- or C-19-functionalized known semisynthetic abietanes against Zika virus, Dengue virus, Herpes virus simplex type 1, and Chikungunya virus are reported. Semisynthetic abietane ferruginol and its analogue 18-(phthalimid-2-yl)ferruginol displayed broad-spectrum antiviral properties. The scale-up synthesis of this analogue has been optimized for further studies and development. This molecule displayed an EC50 between 5.0 and 10.0 μM against Colombian Zika virus strains and EC50 = 9.8 μM against Chikungunya virus. Knowing that this ferruginol analogue is also active against Dengue virus type 2 (EC50 = 1.4 μM, DENV-2), we can conclude that this compound is a promising broad-spectrum antiviral agent paving the way for the development of novel antivirals.